HUMAN FACTORS STUDY OF QMC CLOTHING AND EQUIPMENT DURING COLD WEATHER TESTS OF THE LITTLE JOHN WEAPON SYSTEM - Rosinger, George (1960)
Observations were made on human factors and compatibility problems in relation to the QMC clothing worn by the crew and the equipment of the Little John Weapon System during cold weather tests. The adequacy of the clothing in terms of the protection it afforded the crew, and its compatibility with the equipment have been discussed. Where appropriate, human factors problems were considered in relation to operational efficiency of the equipment.